Assessing the performance of Special Purpose Acquisition Companies (SPACs) in SA and USA: A Comparative Study Treat or Trick? - Maredi, Maakopi Reason (University of the Witwatersrand, Johannesburg, 2023)
This study aimed to investigate the performance of SPACs that are listed in South Africa and in the USA, with a focus on their long run performance after completing their DeSPAC Transactions. The findings indicate that, like previous generations of SPACs in the USA, Third Generation SPACs exhibit poor long run performance after completing their DeSPAC Transactions. However, in the short run, positive cumulative abnormal returns were observed surrounding their DeSPAC Transaction announcements. In relation to SPACs listed in South Africa, similar results are observed, although SPACs listed in South Africa exhibit smaller positive cumulative abnormal returns surrounding their transaction announcements when estimated over a three-day event window in comparison to their USA counterparts. The study also found that sponsor earnouts had a positive relationship with long run performance, while at-risk capital was found to not be an effective tool to align the interests between SPAC sponsors and investors. Furthermore, no evidence was found that higher redemption rates were associated with poor long run performance, with the study revealing that redemption rates were a function of the market conditions at the time of the DeSPAC Transaction announcement. The study’s contributions are providing new insights into the performance and drivers of performance of Third Generation SPACs and offers empirical evidence for regulators and investors to make informed decisions about SPAC investments. Lastly, the findings provide valuable insights for the JSE who are currently updating SPAC regulations in South Africa
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investment. March 2023
Keywords: SPACs; Abnormal Returns; Special Purpose Acquisition Companie; M&A; Mergers and Acquisitions; CARs; BHARs DeSPAC; UCTD; SDG-8: Decent work and economic growth